Students’ Responses to the Realistic Word Problems and Their Mathematics-Related Beliefs in Primary Education - Hidayatullah, Achmad; Csíkos, Csaba (Pedagogika, 2023)
The main purpose of this study is to investigate students’ reactions when doing realistic word problems based on their implicit beliefs and based on their personal factors. Our study revealed that students tended to choose non-realistic responses by ignoring real-world knowledge and excluding realistic considerations when doing realistic mathematics tasks. There were no significant differences in students’ reactions to word problems according to their attitude, grade, and gender.